Serum alanine aminotransferase predicts the histological course of non‐alcoholic steatohepatitis in Japanese patients. Issue 10 (30th December 2014) - Seko, Yuya; Sumida, Yoshio; Tanaka, Saiyu; Mori, Kojiroh; Taketani, Hiroyoshi; Ishiba, Hiroshi; Hara, Tasuku; Okajima, Akira; Yamaguchi, Kanji; Moriguchi, Michihisa; Mitsuyoshi, Hironori; Kanemasa, Kazuyuki; et al.
Abstract : Aim: Some cases with non‐alcoholic fatty liver disease (NAFLD), particularly non‐alcoholic steatohepatitis (NASH), can ultimately progress to liver cirrhosis. However, studies to clarify factors predictive of histological change in patients with NASH remain scarce. Our aim is to determine predictors of histological progression in Japanese patients with biopsy‐proven NASH. Methods: This retrospective cohort study enrolled 52 patients with NASH who underwent serial liver biopsies. Histological evaluation included NAFLD activity score (NAS) and liver fibrosis. The median interval between initial and second liver biopsies was 968 days. An alanine aminotransferase (ALT) response was defined as a decrease of 30% or more from baseline. Results: Of 52 patients, NAS was ameliorated in 30.8%, deteriorated in 30.8% and remained unchanged in 38.4%. Liver fibrosis was improved in 25.0% of patients, progressed in 25.0% and remained stable in 50.0%. Multivariate analysis identified ALT non‐response as a predictor of deterioration of NAS (hazard ratio [HR], 5.85; P = 0.031) and progression of liver fibrosis (HR, 4.50; P = 0.029). The mean annual rate of fibrosis was 0.002 stages/year overall, increasing to 0.15 stages/year in ALT non‐responders. Conclusion: A lack of reduction in serum ALT level by at least 30% from baseline was a predictor for histological progression in patients with NASH. Serum ALT level is a better predictor of histological change than insulin resistance or bodyweight and can be a valid index in treatment. Serum ALT should be strictly controlled to prevent liver histological progression in patients with NASH.